Efficient Genetic Transformation and Regeneration of a Farmer-Preferred Cassava Cultivar From Ghana - Elegba, Wilfred; McCallum, Emily; Gruissem, Wilhelm; Vanderschuren, Hervé (Frontiers in Plant Science, 2021)
Cassava is an important staple crop that provides food and income for about 700 million Africans. Cassava productivity in Africa is limited by viral diseases, mainly cassava mosaic disease (CMD) and cassava brown streak disease (CBSD). Genetic barriers such as high heterozygosity, allopolyploidy, poor seed set and irregular flowering constrain the development of virus-resistant cassava varieties via conventional breeding. Genetic transformation represents a valuable tool to circumvent several challenges associated with the development of virus resistance and other valuable agronomic traits in cassava. The implementation of genetic transformation in many local African cultivars is limited either by the difficulty to produce friable embryogenic callus (FEC), low transformation, and/or regeneration efficiencies. Here we report the successful induction of organized embryogenic structures (OES) in eleven farmer-preferred cultivars locally grown in Ghana. The production of high quality FEC from one local cultivar, ADI 001, facilitated its genetic transformation with high shoot regeneration and selection efficiency, comparable to the model cassava cultivar 60444. We show that using flow cytometry for analysis of nuclear ploidy in FEC tissues prior to genetic transformation ensures the selection of genetically uniform FEC tissue for transformation. The high percentage of single insertion events in transgenic lines indicates the suitability of the ADI 001 cultivar for the introduction of virus resistance and other useful agronomic traits into the farmer-preferred cassava germplasm in Ghana and Africa.